Control of anthracnose in fruits of Persea Americana Miller treated with essential oils - Oliveira, Valdeir de Souza; Porcino, Mirelly Miguel; Nascimento, Luciana Cordeiro do; Jovino, Raphael Silva; Alves, Bruna Laís Nascimento (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
Anthracnose is a disease caused by the pathogen Colletotrichum gloeosporioides affects avocado fruits (Persea americana Miller), making them unfit for commercialization. The aim of this study was to determine the effect of essential oils on the control of anthracnose in avocado fruits and its influence on the physico-chemical quality. The work was conducted at the Phytopathology Laboratory - UFPB, campus II. The fruits of avocado were treated with essential oils of lemon grass, cinnamon, eucalyptus, ricin, copaiba, andiroba, rosemary, canola, clove and flaxseed, which were added to the BDA culture medium at a concentration of 0.75 μLmL-1 and added to these two drops of Tween 80. In addition to the fungicide Tiabendazole 400 ml / 100 L added in the BDA medium and the control (pure culture medium). The following were evaluated: index of mycelial growth rate, conidia production and pathogen severity. The physical-chemical evaluations of the fruits were: loss of fresh mass; peel strength; pH; SS / AT ratio. The essential oils of cinnamon, lemon grass, eucalyptus, cloves, fennel, copaiba and rosemary reduce mycelial growth. The oils used show potential as an alternative treatment reducing the use of fungicides. Cinnamon oil in the concentration 0.75 μLmL-1 significantly reduces the growth and sporulation of the pathogen. Essential oils do not interfere with post-harvest quality of avocado fruits P. americana Miller.